IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DALAM PEMBELAJARAN BAHASA INDONESIA BERBASIS KEARIFAN LOKAL - Muhammad Baidhawi; Aswandikari Aswandikari; Burhanuddin Burhanuddin (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
This study aims to identify and analyze the implementation of the Independent Curriculum (Kurikulum Merdeka) from the aspects of planning, execution, and evaluation in Indonesian language learning based on local wisdom, as applied at SMP Negeri 1 Bayan. A qualitative approach was used in this research. Data collection techniques involved direct observation, analyzed using the interactive model of Miles and Huberman. The results indicate that the planning stage has been executed very well, meeting the criteria outlined in six indicators on the observation instrument for planning. The planning activities carried out by teachers include the preparation of teaching modules, Learning Outcomes (Capaian Pembelajaran or CP), formulation of Learning Objectives (Tujuan Pembelajaran or TP), development of the Learning Objectives Flow (Alur Tujuan Pembelajaran or ATP), and design of instructional steps, learning media, and assessment tools for student learning. At the implementation stage, the curriculum was also executed very well, meeting the criteria outlined in twenty-nine indicators in the observation instrument for implementation. In this regard, the form of curriculum implementation in Indonesian language learning involved the teacher delivering instruction based on the prepared Indonesian language module, specifically a letter-text module designed in the planning phase. At the evaluation stage, the curriculum implementation was carried out very effectively, meeting the criteria in the observation instrument for evaluation, which includes diagnostic evaluation, formative assessment, and summative assessment.